Just passing through? Inhibition of return in saccadic sequences. Issue 2 (February 2015) - MacInnes, W. Joseph; Krüger, Hannah M.; Hunt, Amelia R.
Responses tend to be slower to previously fixated spatial locations, an effect known as "inhibition of return" (IOR). Saccades cannot be assumed to be independent, however, and saccade sequences programmed in parallel differ from independent eye movements. We measured the speed of both saccadic and manual responses to probes appearing in previously fixated locations when those locations were fixated as part of either parallel or independent saccade sequences. Saccadic IOR was observed in independent but not parallel saccade sequences, while manual IOR was present in both parallel and independent sequence types. Saccadic IOR was also short-lived, and dissipated with delays of more than ∼1500 ms between the intermediate fixation and the probe onset. The results confirm that the characteristics of IOR depend critically on the response modality used for measuring it, with saccadic and manual responses giving rise to motor and attentional forms of IOR, respectively. Saccadic IOR is relatively short-lived and is not observed at intermediate locations of parallel saccade sequences, while attentional IOR is long-lasting and consistent for all sequence types.